Determinants of Consumer Sector Company Value: Evidence from CSR and Financial Decisions: Penentu Nilai Perusahaan Sektor Konsumsi: Bukti dari CSR dan Keputusan Keuangan - Nugroho, Hendy Nurwahyu; Maryanti, Eny (Universitas Muhammadiyah Sidoarjo, 2025)
General Background The primary goal of a company is to maximize firm value, which is crucial for stakeholder welfare and is often reflected in stable and high share prices. Specific Background The Indonesian consumer manufacturing sector experienced stock price fluctuations during the 2019–2022 COVID-19 period, raising questions about which internal factors primarily govern firm valuation. Knowledge Gap Existing literature shows inconsistent results regarding the relationship between Corporate Social Responsibility (CSR), environmental performance, investment, and funding decisions on firm value, necessitating contextual re-examination. Aims This study examines the relationships of CSR, environmental performance, investment decisions, and funding decisions on firm value in consumer manufacturing companies listed on the IDX from 2019–2022. Results Quantitative analysis of 12 sampled companies revealed that CSR, investment decisions, and funding decisions significantly determine firm value. Conversely, environmental performance demonstrated no significant relationship. Novelty This research contributes by testing this comprehensive set of variables within the specific context of the consumer sector during the unique economic conditions of the COVID-19 pandemic. Implications The findings suggest that for this sector and period, social disclosure and financial signaling are more critical to investor valuation than environmental initiatives. Highlights : CSR and corporate financial policies are significant determinants of firm value. Environmental performance does not affect firm value during the 2019-2022 period. Investment and funding decisions serve as positive signals for future company prospects. Keywords: CSR, Firm Value, Investment Decisions, Funding Decisions, Consumer Sector